Participate in a Broader Sense? Thoughts on Swedish Contract Archaeology and Approaches to the Public in the Light of the Excavations in Motala 1999–2013 - Anna Arnberg; Göran Gruber (Current Swedish Archaeology, 2014)
Whether and, if so, how archaeology can create meaning and value in society is a long and ongoing debate. Due to a rewriting of the Swedish law on cultural heritage, and the rhetoric of the national authorities stressing society’s extended expecta tions of the practice, the topic is more current than ever for Swedish contract archaeology. In a case study this paper addresses the subject from a local perspective, focusing on the use of archaeology and approaches to the public. It is argued that contract archaeology has better potential to fulfil its pub lic assignment than is utilized today, but will need to upgrade its selfimage and embrace more varied approaches to the public.